Effects of progesterone and testosterone on the hyaluronidase activities and sperm characteristics in sheep - Tanyildizi, S; Bozkurt, T (Tubitak Scientific & Technological Research Council Turkey, 2002)
The aim of this study was to determine the effects of progesterone and testosterone hormones on the hyaluronidase activities of serum and semen and on sperm characteristics in sheep. Thirty healthy Akkaraman sheep were used. The progesterone and testosterone were injected intramuscularly at the rate of 0.5 mg/kg and 5 mg/kg, respectively. Then the blood and semen samples were obtained from the sheep at 1, 2, 4, 24, 48, 72 and 168 In. The serum hyaluronidase activities of ewes and rams in progesterone and testosterone groups increased significantly (p < 0.01, p < 0.001) when compared with the control groups at all times. Additionally, there were significant (p < 0.001) increases in the levels of semen hyaluronidase activity in the progesterone group except at 4 h. Furthermore, semen hyaluronidase activities in the testosterone group were detected to decrease significantly (p < 0.01) in comparison with the control rams except at 4 In. The use of progesterone and testosterone caused a significant (p < 0.05, p < 0.01) increase in spermatozoa motility, respectively. However, sperm concentrations were determined to decrease significantly (p < 0.01, p < 0.001) in both groups. Although the values for semen volume decreased significantly (p < 0.05, p < 0.01) in the progesterone group, the same values were observed to increase significantly (p < 0.01) in the testosterone group except at 48 h when compared with the control groups. The results of this study showed that there were no significant correlations between semen hyaluronidase activities and sperm characteristics. In conclusion, the use of both hormones did not have any deleterious effects on hyaluronidase activities but for the semen samples in the testosterone groups. However, progesterone and testosterone hormones cause harmful effects on the fertilization ability of rams due to decreased sperm concentration values.
Keywords: hyaluronidase; spermatozoa; motility; sheep